In vitro Evaluation of Apical Debris Extrusion in Primary Teeth Using Rotary and Hand Files - Shaila Chaudhary; Nikhil Patel; Harshangi Patel; Apoorva Mamindla; Medum Shabharish S. Kumar; K. Vishnu Prasad; Shivani Shandilya (Journal of Pharmacy and Bioallied Sciences)
Aim: This research used two distinct pediatric rotary files and traditional manual files for evaluation and contrast of the amount of apically extruded debris during root canal cleaning in deciduous teeth. Materials and Methods: Thirty maxillary deciduous central incisors that showed no symptoms of resorption were removed and enrolled in the study. Three distinct file systems were used in the preparation of the canals: Group 1: Manual K-files (Uniflex NiTi K-Files), Group 2: Kedo SG Blue files (Kedo Dental, Chennai, India), and Group 3: Pro AF baby gold files (Kids-e-Dental, India). Apical extrusion was gathered and desiccated in Eppendorf tubes that had been previously weighed. The weight measured preoperative was deducted from the postoperative weight to get the dry weight. To examine the data’s statistics, we applied a one-way ANOVA with Tukey’s post hoc test. Results: Rotary file systems produced considerably a lesser debris extrusion than the hand files (P < 0.05). Conclusion: Debris was apically ejected from primary teeth by all the groups. The extrusion of debris apically was reduced while using Pro AF baby gold files.